Mass cytometry reveals immune signatures associated with cytomegalovirus (CMV) control in recipients of allogeneic haemopoietic stem cell transplant and CMV‐specific T cells. Issue 7 (2nd July 2020) - McGuire, Helen M; Rizzetto, Simone; Withers, Barbara P; Clancy, Leighton E; Avdic, Selmir; Stern, Lauren; Patrick, Ellis; Fazekas de St Groth, Barbara; Slobedman, Barry; Gottlieb, David J; Luciani, Fabio; Blyth, Emily
Abstract: Objectives: Cytomegalovirus (CMV) is known to have a significant impact on immune recovery post‐allogeneic haemopoietic stem cell transplant (HSCT). Adoptive therapy with donor‐derived or third‐party virus‐specific T cells (VST) can restore CMV immunity leading to clinical benefit in prevention and treatment of post‐HSCT infection. We developed a mass cytometry approach to study natural immune recovery post‐HSCT and assess the mechanisms underlying the clinical benefits observed in recipients of VST. Methods: A mass cytometry panel of 38 antibodies was utilised for global immune assessment (72 canonical innate and adaptive immune subsets) in HSCT recipients undergoing natural post‐HSCT recovery ( n  = 13) and HSCT recipients who received third‐party donor‐derived CMV‐VST as salvage for unresponsive CMV reactivation ( n  = 8). Results: Mass cytometry identified distinct immune signatures associated with CMV characterised by a predominance of innate cells (monocytes and NK) seen early and an adaptive signature with activated CD8 + T cells seen later. All CMV‐VST recipients had failed standard antiviral pharmacotherapy as a criterion for trial involvement; 5/8 had failed to develop the adaptive immune signature by study enrolment despite significant CMV antigen exposure. Of these, VST administration resulted in development of the adaptive signature in association with CMV control in three patients. Failure to respond to CMV‐VST in one patient was associated with persistent absence of the adaptive immune signature. Conclusion: The clinical benefit of CMV‐VST may be mediated by the recovery of an adaptive immune signature characterised by activated CD8 + T cells. Abstract : In this study, immune profiling with mass cytometry identified immune signatures associated with cytomegalovirus (CMV) reactivation after allogeneic stem cell transplant in patients undergoing natural immune recovery. Failure to control CMV was associated with failure to develop an adaptive immune signature that could be reversed with third‐party CMV virus‐specific T cells in some recipients.